Aichryson santamariensis (Crassulaceae): a new species endemic to Santa Maria in the Azores - Moura, Mónica; Carine, Mark; Menezes De Sequeira, Miguel (Phytotaxa, 2015)
A new species of Aichryson, A. santamariensis, is described. The species is endemic to the island of Santa Maria in the Azores. Analysis of molecular (ITS and trnL-F) and morphological data support the segregation of this new species from A. villosum with which it was formerly considered conspecific. Aichryson santamariensis differs from A. villosum by characters including indumentum, leaf shape, seed shape and its generally smaller size.